2020
DOI: 10.5194/mr-1-75-2020
|View full text |Cite
|
Sign up to set email alerts
|

Distance measurement between trityl radicals by pulse dressed electron paramagnetic resonance with phase modulation

Abstract: Abstract. Distance measurement in the nanometre range is among the most important applications of pulse electron paramagnetic resonance today, especially in biological applications. The longest distance that can be measured by all presently used pulse sequences is determined by the phase memory time Tm of the observed spins. Here we show that one can measure the dipolar coupling during strong microwave irradiation by using an appropriate frequency- or phase-modulation scheme, i.e. by applying pulse sequences i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In our work, we have chosen the I-BURP class of band-selective inversion pulses (Geen and Freeman, 1991) that shows a very sharp inversion profile. Similar approaches using resonant rf irradiation in nested rotating frames have been reported before in liquid-state NMR (Grzesiek and Bax, 1995), in recoupling experiments in solid-state NMR (Khaneja and Nielsen, 2008;Straasø et al, 2009), and in EPR (Wili et al, 2020).…”
Section: Introductionmentioning
confidence: 64%
“…In our work, we have chosen the I-BURP class of band-selective inversion pulses (Geen and Freeman, 1991) that shows a very sharp inversion profile. Similar approaches using resonant rf irradiation in nested rotating frames have been reported before in liquid-state NMR (Grzesiek and Bax, 1995), in recoupling experiments in solid-state NMR (Khaneja and Nielsen, 2008;Straasø et al, 2009), and in EPR (Wili et al, 2020).…”
Section: Introductionmentioning
confidence: 64%
“…This approach has allowed structure and dynamics of these bio-molecules to be studied in order to better understand their biomolecular functions under native conditions. [131][132][133][134][135] Finally, it has been shown that trityl radicals are also suitable for EPR imaging.…”
Section: Optical Applications For Ptm Radicalsmentioning
confidence: 99%
“…After the concept of LEACH clustering protocol is put forward, the energy saving property and network lifetime of network nodes have been greatly improved. However, the application of LEACH protocol in the training distance collection of longdistance runners has its own limitations that cannot be ignored [10]. On the basis of the LEACH protocol, this paper introduces an energy balanced clustering routing algorithm based on energy and location, which fully considers the energy and location factors of nodes in the cluster head election mechanism, avoids the nodes with low residual energy and poor geographical location from being selected as the cluster head node, effectively balances the energy consumption distribution of nodes, prolongs the network life cycle, and optimizes the training distance of long-distance runners from the collection efficiency, so as to realize realtime collection of long-distance athletes' training distance [11][12][13].…”
Section: Energy Balanced Clustering Routing Algorithm Based Onmentioning
confidence: 99%